Pengembangan E-book Interaktif sebagai Bahan Ajar Berbasis Hasil Riset Tumbuhan Lumut di Danau Mooat Kabupaten Bolaang Mongondow Timur - Mega Anastasya Diska Mokoginta; Elya Nusantari; Jusna Ahmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Biodiversity represents the condition and level of ecosystem complexity in a particular area, reflecting the presence of various living organisms and their interactions with the environment. Based on its ecological conditions, Mooat Lake in East Bolaang Mongondow Regency serves as a habitat for various plant species, one of which is moss (Bryophyta), which plays an important role in maintaining ecosystem balance. The presence of Bryophyta in this area has the potential to be utilized as a contextual learning resource in biology education. This study aims to determine the validity level of an interactive e-book based on Bryophyta research conducted at Mooat Lake, East Bolaang Mongondow Regency, as a biology learning material for tenth-grade senior high school students. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. The product developed in this study was an interactive e-book containing biodiversity material based on field research findings. The results showed that the material expert validation obtained a percentage of 94.2%, categorized as very valid, while the media expert validation obtained a percentage of 83.7%, also categorized as very valid. Based on these findings, it can be concluded that the interactive e-book based on moss research meets the criteria of being very valid and is suitable for use as a learning resource in biology subjects, particularly on biodiversity topics.